The visinin-like proteins VILIP-1 and VILIP-3 in Alzheimer's disease—old wine in new bottles - Braunewell, Karl H. (Frontiers in Molecular Neuroscience, 2012)
The neuronal Ca2+-sensor proteins, VILIP-1 and VILIP-3 (gene names VSNL1 and HPCAL1), have been implicated in the etiology of Alzheimer’s disease (AD). In AD brains, expression of proteins and mRNA is down-regulated. Reduced hippocampal VILIP-1 mRNA levels correlate with the content of neurofibrillary tangles (NFT) and amyloid plaques - the pathological characteristics of AD, and with the mini mental state exam (MMSE), a test for cognitive impairment. Recently, VILIP-1 was identified as a cerebrospinal fluid (CSF) biomarker for AD. Its increased CSF levels correlate with levels of Abeta, tau, ApoE4, and reduced MMSE scores. Moreover, genome-wide association studies (GWAS) show association of VSNL1 and HPCAL1 loci with AD+P (+psychosis) and late onset AD (LOAD), respectively. VILIP-1 is involved in pathological mechanisms of altered Ca2+-homeostasis, including enhanced tau phosphorylation and cell death, depending on co-expression with the neuroprotective Ca2+ buffer calbindin D28K. VILIP-1 affect pathways, such as cyclic nucleotide signalling and dendritic growth, as well as nicotinergic modulation of neuronal network activity, both of which regulate synaptic plasticity and cognition. The interaction partner of VILIP-1, alpha4beta2 nicotinic acetylcholine receptor, is severely reduced in AD. Comparatively little is known about VILIP-3. It interferes with MAPK signaling and interacts with cytochrome b5, an enzyme belonging to the plasma membrane redox system (PMRS). The PMRS, which provides electrons for the recycling of antioxidants, is impaired in AD. A current hypothesis is that the reduced expression of VILIPs in AD reflects Ainduced down-regulation of their expression, and indicates selective vulnerability of subpopulations of neurons, such as hippocampal interneurons. The down-regulation attenuates neuronal signal pathways regulating the functions of dendrites and neuroplasticity, and as a consequence, this may contribute to the cognitive decline in AD.